Pretreatment Hemoglobin as an Independent Prognostic Factor in Primary Central Nervous System Lymphomas. (13th March 2019) - Le, My; Garcilazo, Ytel; Ibáñez‐Juliá, Maria‐José; Younan, Nadia; Royer‐Perron, Louis; Benazra, Marion; Mokhtari, Karima; Houillier, Caroline; Hoang‐Xuan, Khê; Alentorn, Agusti
Abstract: Background: Primary central nervous system lymphoma (PCNSL) is a rare subtype of extranodal lymphoma. Despite established clinical prognostic scoring such as that of the Memorial Sloan Kettering Cancer Center (MSKCC) and the International Extranodal Lymphoma Study Group, outcome prediction needs to be improved. Several studies have indicated an association between changes in hematologic laboratory parameters with patient outcomes in PCNSL. We sought to assess the association between hematological parameters and overall survival (OS) in patients with PCNSL. Methods: Pretreatment blood tests were analyzed in patients with newly diagnosed PCNSL ( n  = 182), and we divided the analysis into two cohorts (A and B, both n  = 91). OS was evaluated using the Cox proportional hazards models and log‐rank test. Furthermore, the accuracy of the different multivariate models was assessed by Harrell's concordance index (C‐index). Results: Using prechemotherapy blood tests, anemia was found in 38 patients (41.8%) in cohort A and 34 patients (37.4%) in cohort B. In univariate analysis, anemia (<12 g/dL in women and <13 g/dL in men) was significantly associated with OS. None of the other blood tests parameters (neutrophils, lymphocyte, or platelets counts) or their ratios (neutrophil‐to‐lymphocyte ratio and neutrophil‐to‐platelets ratio) were associated with OS. In multivariate analysis, after adjusting by MSKCC score, anemia remained an independent prognostic factor. Interestingly, the prediction accuracy of OS using Harrell's C‐index was similar using anemia or MSKCC (mean C‐index, 0.6) and was increased to 0.67 when combining anemia and MSKCC. Conclusion: The presence of anemia was associated with poor prognosis in both cohorts of PCNSL. Validation of these results and biologic role of hemoglobin levels in PCNSL requires further investigation. Implications for Practice: The prediction of the outcome of primary central nervous system lymphoma (PCNSL) using the most frequently used scores (i.e., Memorial Sloan Kettering Cancer Center [MSKCC] or International Extranodal Lymphoma Study Group) needs to be improved. We analyzed a large cohort of PCNSL to dissect the potential prognostic value of blood tests in this rare entity. We found anemia as an independent predictor for overall survival in PCNSL. Interestingly, the accuracy to predict PCNSL outcome was improved using hemoglobin level. This improvement was additional to the currently used clinical score (i.e., MSKCC). Finally, none of the other blood tests parameters or their ratios had a prognostic impact in this study. Abstract : This article assesses the association of hematologic parameters before starting high‐dose methotrexate‐based chemotherapy with the clinical evolution of primary central nervous system lymphoma, providing insight on the potential clinical value of blood test results as a simple surrogate marker of clinical outcome in this rare lymphoma.